Implementasi Sistem Analytics pada Produk menggunakan OLAP berbasis MongoDB - Dwi Payana, I Kadek Krisna; Rahning Putri, Luh Arida Ayu (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Technology right now can knowing user what they want or find out. that kind of technology using analytics for knowing what user often see or recently visited. Users visited some product that will be tracked and saved that data for analytics. Using Online Analytical Processing (OLAP) can lower traffic for database Online Transactional Database (OLTP) for purposing database analytics only. Splitting traffic for transaction request and analytics request and make structured database. This system using golang as main programming language and can communication to client services (Web or Android).